Characterization of the co-purified invertase and beta-glucosidase of a multifunctional extract from Aspergillus terreus - Giraldo, Marielle Aleixo [UNESP]; Goncalves, Heloisa Bressan [UNESP]; Melo Furriel, Rosa dos Prazeres; Jorge, Joo Atilio; Souza Guimares, Luis Henrique (Springer, 2014)
The filamentous fungus Aspergillus terreus secretes both invertase and beta-glucosidase when grown under submerged fermentation containing rye flour as the carbon source. The aim of this study was to characterize the co-purified fraction, especially the invertase activity. An invertase and a beta-glucosidase were co-purified by two chromatographic steps, and the isolated enzymatic fraction was 139-fold enriched in invertase activity. SDS-PAGE analysis of the co-purified enzymes suggests that the protein fraction with invertase activity was heterodimeric, with subunits of 47 and 27 kDa. Maximal invertase activity, which was determined by response surface methodology, occurred in pH and temperature ranges of 4.0-6.0 and 55-65 A degrees C, respectively. The invertase in co-purified enzymes was stable for 1 h at pH 3.0-10.0 and maintained full activity for up to 1 h at 55 A degrees C when diluted in water. Invertase activity was stimulated by 1 mM concentrations of Mn2+ (161 %), Co2+ (68 %) and Mg2+ (61 %) and was inhibited by Al3+, Ag+, Fe2+ and Fe3+. In addition to sucrose, the co-purified enzymes hydrolyzed cellobiose, inulin and raffinose, and the apparent affinities for sucrose and cellobiose were quite similar (K-M = 22 mM). However, in the presence of Mn2+, the apparent affinity and V-max for sucrose hydrolysis increased approximately 2- and 2.9-fold, respectively, while for cellobiose, a 2.6-fold increase in V-max was observed, but the apparent affinity decreased 5.5-fold. Thus, it is possible to propose an application of this multifunctional extract containing both invertase and beta-glucosidase to degrade plant biomass, thus increasing the concentration of monosaccharides obtained from sucrose and cellobiose.
Keywords: Invertase; Aspergillus; beta-glucosidase; Fructofuranosidase; Multifunctional extract